PENGARUH KOMPONEN ASET DAN KEWAJIBAN PAJAK TANGGUHAN TERHADAP BEBAN PAJAK KINI MASA DEPAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2005-2011) - Sari, Reny Kartika; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of the components of deferred tax assets and liabilities for future current tax over a three-year period (t+1, t+2, t+3). Deferred tax assets and liabilities arising from timing differences in the recognition of revenues and expenses based on financial accounting standards and tax laws. Deferred tax assets and deferred tax liabilities are recognized in the financial statements because it can lead to future tax payments to be larger or smaller. Sample of this study consists of 88 companies from manufacturing sectors listed on Indonesia Stock Exchange in 2005-2011. Multiple regression analysis is used to determine the effect of each component of deferred tax assets and liabilities for future current tax. The results show that deferred tax assets of post-employment benefits has negatively significant and deferred tax liabilities of accelerated depreciation has positively significant to future current tax. While the results for the deferred tax assets of accrued expenses do not affect future current tax. Future taxes paid related to the time reversal of deferred tax assets and liabilities. Accrued expenses may not be realized over a three-year period, so the deferred tax assets do not reverse.